Toxocara canis infection and its importance in animal and public health: a review - Alvarado-Borja, Valeria (2023)
The Toxocara canis parasite represents a worldwide public health problem. This agent is an ascarid that, in its adult stage, lives in the small intestine of the domestic dog and several wild canids; it presents a complex biological cycle that ensures its transmission and permanence in the hosts it affects; in its intestinal phase, it causes mechanical, irritative and obstructive action, interfering in the transit and digestion of food. Toxocariasis affects young dogs and cats; it produces respiratory signs (cough due to migration of pulmonary larvae), growth retardation (emaciation, weakening of the coat and arthralgia) and intestinal disorders (alternating diarrhea and constipation, abdominal bulging, and vomiting). More intense prenatal infections in puppies can lead to severe disease with alternating diarrhea and constipation, vomiting, typical "pot belly," reduced growth with cachexia, poor coat and, in some cases, death. It has been reported to be present in public park soils, where it contaminates the environment and becomes a source of infection for people. In dog infections, especially strays, nematodes are an important epidemic factor. Regarding human infection, the process tends to become a chronic condition with a broad spectrum of clinical manifestations, from an asymptomatic course to characteristic forms of clinical presentations, such as visceral, ocular, neurological, and covert larva migrans. Regarding control and prevention, health education should be considered to modify the risk practices of pet owners and the community.